2017
DOI: 10.4209/aaqr.2017.03.0095
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variation of PM2.5 and Atmospheric PCDD/Fs in Northern Taiwan during Winter Monsoon and Local Pollution Episodes

Abstract: Winter monsoonal air masses traveling from Inner Mongolia to downwind nations can transport cold temperature and air pollutants. This study investigated the effects of the long-range transport (LRT) of air pollutants by northeastern monsoons and local pollution (LP) episodes on atmospheric PM 2.5 , polychlorinated dibenzo-p-dioxin (PCDD), and polychlorinated dibenzofuran (PCDF) concentrations in northern Taiwan during the winters of 2014 and 2015. Air samples were collected in rural (Rural Site 1 was mountaino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
(80 reference statements)
0
6
1
Order By: Relevance
“…The PM 2.5 concentrations measured from LRT event (Site A), local urban traffic emission (Site B), and night market (Site C) were found to be 39.0 µg/m 3 , 42.9 µg/m 3 , and 28.3 µg/m 3 , respectively (Table S3). The PM 2.5 concentrations found in this study (28.3-42.9 µg/m 3 ) was lower than that found in central Taiwan (33.2-76.4 µg/m 3 ) [27] but higher than a two-year observation of PM 2.5 concentration at urban area of Taipei (20.5-21.4 µg/m 3 ) [20]. We observed highest PM 2.5 concentrations at traffic area (42.9 µg/m 3 ) which was located in the center of Taipei city.…”
Section: Pm 25 Concentrations and Characteristics Measured At Differcontrasting
confidence: 86%
See 3 more Smart Citations
“…The PM 2.5 concentrations measured from LRT event (Site A), local urban traffic emission (Site B), and night market (Site C) were found to be 39.0 µg/m 3 , 42.9 µg/m 3 , and 28.3 µg/m 3 , respectively (Table S3). The PM 2.5 concentrations found in this study (28.3-42.9 µg/m 3 ) was lower than that found in central Taiwan (33.2-76.4 µg/m 3 ) [27] but higher than a two-year observation of PM 2.5 concentration at urban area of Taipei (20.5-21.4 µg/m 3 ) [20]. We observed highest PM 2.5 concentrations at traffic area (42.9 µg/m 3 ) which was located in the center of Taipei city.…”
Section: Pm 25 Concentrations and Characteristics Measured At Differcontrasting
confidence: 86%
“…The PCDD/F concentration during LRT event in this study was found to be much lower than our previous measurement at the same area. PCDD/F concentrations in 2014 and 2015 during LRT event at Fugui Cape station were found to be 16.4-28.9 fg I-TEQ/m 3 [20].…”
Section: Pm 25 Concentrations and Characteristics Measured At Differmentioning
confidence: 92%
See 2 more Smart Citations
“…Local emission sources of air pollutants in the TKMA include vehicular exhaust, industrial emissions, and various sources related to residential activities (e.g., cooking) Ho et al, 2018;Wu et al, 2017). In winter time, the long-distance transport of dust and polluted air masses under the northeast monsoon from the Asian continent results in a significant increase in concentrations of air pollutants (Chi et al, 2017;Chou et al, 2010).…”
Section: Study Areamentioning
confidence: 99%